Optimalisasi Fungsi Lahan Perkampungan Sebagai Sumber Ketahanan Pangan Nasional di Kampung Mosso, Jayapura - Sudiro; Tommi; Kasim Samosir, Rasi (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to identify the availability of undeveloped land in Mosso Village as a medium for farming or gardening, analyze the suitability of optimal agricultural land or plantations in Mosso Village based on the Jayapura City Regional Spatial Plan (RTRW), and determine the direction of optimized space utilization as agricultural land and plantations in Mosso Village. The background of this research is based on the potential of Mosso Village as the outermost and foremost area that has the potential of agriculture and plantations as a source of food security. The method carried out in this study uses a descriptive – exploratory method